Party cues in elections under multilevel governance: Theory and evidence from US states - Benny Geys; Jan Vermeir (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2012)
In federal countries, competence for policy matters is often shared between various levels of government. As only overall outcomes are observed, this might blur accountability by decreasing voters' ability to infer information about the performance of their leaders. In this article, we analyse how party cues (i.e., politicians' party membership acting as a cue towards their characteristics) affect voters' incomplete information about politicians in a federal setting. We first of all show that party cues allow indirect inference regarding politicians using observed policy outcomes, alleviating the accountability problem. Empirical evidence from US presidential election results across all 50 US states over the period 1972-2008 provides support for this proposition. Yet, while the availability of party cues in a federal setting increases the national incumbents' effort in some cases, it may reduce effort particularly when the regional incumbent if of a different party.
Keywords: D72; H30; H77; 330; federalism; accountability; multilevel governance; party cues; Politiker; Politische Partei; Föderalismus; Wahlverhalten; USA